(untitled) (Journal of Economic Research & Business Administration, 2016)
This article discusses the main challenges for the transport of interna-tional transport corridors. Existing transport capacity and the development of transit along the transport corridors is of great importance for countries within the Community. In the article are shown the problems existing in member states of EAES, creating difficulties for full development of inte-gration of motor and railway transport. Investigated a number of physical and non-physical barriers to transport corridors and are given tasks that can improve the efficiency of the transport system, it is necessary for the growth and competitiveness of the economy.